Buddhism, equality and feminism: Embodied practices - Lai, S.Y. (2017)
This paper explores the connection between notions and meanings of Buddhism, equality, and feminism as embodied practices, based on our grounded experiences at the ideal and personal levels. It engages with discourses that question the use of the terms feminism or equality in relation to representations of what it means to be a Buddhist or a Buddhist nun, deeming them colonialist or an imposition by Western ideals and notions. While acknowledging the contribution of postcolonial studies that critique the representation of Asian or non-Western women as monolithic, static, or the exotic other, this paper argues that notions of equality and feminism are not alien to non-Western nations. In fact, there is a diversity of what it means to be Asian and this does not necessarily exclude notions of equality and feminism. Similarly, to be a Buddhist or a Buddhist nun does not necessarily exclude these notions. In fact, based on my experiences of doing research and my engagement to support the establishment of the female monastic order in Thailand and Malaysia, this paper argues that, in fact, there are those who identify as feminists that support such initiatives and may become nuns themselves, whether temporarily or permanently. However, the ways in which they frame themselves or position themselves and their initiatives depend on social context and timing. The paper problematizes the diversity and fluidity of what it means to be a Buddhist and a feminist in the Asian context and, at the same time, engages with the intersection of postcolonialism, gender, and religious studies.